2019
DOI: 10.15446/rsap.v21n1.68395
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sensorineural hearing loss in newborns in a hospital from a developing country

Abstract: Objective This study aimed to determine the prevalence of nonsyndromic congenital sensorineural hearing loss at the Hospital Universitario San Ignacio, Bogotá, Colombia, and to describe the risk factors associated with this condition.Materials and Methods A prospective, observational cross-sectional study with bivariate analysis was conducted. A three-phase process using the Otoacoustic Emissions test screened all live newborns between June 2013 and June 2014. Negative cases were confirmed by Automated Auditor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…meningitis), trauma or chemotherapy, and caregiver concern. Table 3 shows the number of studies that reported each JCIH risk factor according to WHO region, the number of studies that conducted statistical analysis to determine if that risk factor was associated with hearing loss in their sample, and whether those analyses found significant associations 34–54 …”
Section: Resultsmentioning
confidence: 99%
“…meningitis), trauma or chemotherapy, and caregiver concern. Table 3 shows the number of studies that reported each JCIH risk factor according to WHO region, the number of studies that conducted statistical analysis to determine if that risk factor was associated with hearing loss in their sample, and whether those analyses found significant associations 34–54 …”
Section: Resultsmentioning
confidence: 99%
“…Regarding the accuracy of hearing-screening, it is evident that the ABR has 100% sensitivities and 97.2% specificities; whereas the OAE have 50% sensitivities and 49.1% specificities (Manikam et al , 2017). Previous studies showed that increasing the age at early screening and retests reduces the number of referral cases (Akinpelu et al , 2014; Ospina-Garcia et al , 2020). Similarly, screenings having higher frequencies had lowered the referral cases.…”
Section: Discussionmentioning
confidence: 99%
“…and other risk factors such as hypoxia at birth, hyperbilirubinemia, prematurity, and being treated in the neonatal intensive care unit (NICU) for 5 days [14]. Research conducted by Juan C. Ospina (2019) in Colombia, the etiology of congenital sensorineural deafness is often reported with unknown causes (37.7%), non-syndromic genetics (29.2%), syndromic genetics (3.2%), prenatal (12%), perinatal (9.6%), and postnatal (8.2%) [15,16]. Based on the high percentage of prenatal sensorineural deafness, the researchers felt it was important to know the relationship between prenatal risk factors and sensorineural deafness in children at the ENT-Head and Neck Polyclinic at RSUDZA Banda Aceh.…”
Section: Introductionmentioning
confidence: 99%